Surface-dominant transport in Weyl semimetal NbAs nanowires for next-generation interconnects - Yeryun Cheon; Mehrdad T. Kiani; Yi-Hsin Tu; Sushant Kumar; Nghiep Khoan Duong; Jiyoung Kim; Lingcheng Kong; Quynh P. Sam; Han Wang; Satya K. Kushwaha; Nicholas Ng; Seng Huat Lee; et al. (Science, 2026)
Ongoing demands for smaller and more energy-efficient electronic devices necessitate alternative interconnect materials with lower electrical resistivity at reduced dimensions. We report the synthesis of Weyl semimetal niobium arsenide (NbAs) nanowires through thermomechanical nanomolding with single crystallinity and controlled diameters down to 40 nanometers. The resistivity of NbAs nanowires decreases with decreasing diameter, and 40-nanometer-diameter nanowires exhibited a room-temperature resistivity of 10.5 ± 1.9 microhm·centimeters, which is ~70% lower than their bulk counterpart. Calculations attribute this resistivity reduction to surface-dominant conduction with a long carrier lifetime at finite temperatures. Further characterization of nanowires and bulk crystals revealed high breakdown current density, stability, and thermal conductivity. These properties highlight the potential of NbAs nanowires as next-generation interconnects that could surpass the limitations of current copper-based interconnects.